2016
DOI: 10.1371/journal.ppat.1006135
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of Cytolytic Potential in SIV-Specific CD8+ T Cells Following Acute SIV Infection in Rhesus Macaques

Abstract: Poor maintenance of cytotoxic factor expression among HIV-specific CD8+ T cells, in part caused by dysregulated expression of the transcription factor T-bet, is associated with HIV disease progression. However, the precise evolution and context in which CD8+ T cell cytotoxic functions become dysregulated in HIV infection remain unclear. Using the rhesus macaque (RM) SIV infection model, we evaluated the kinetics of SIV-specific CD8+ T cell cytolytic factor expression in peripheral blood, lymph node, spleen, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…They further showed that repopulation of CD8 T cells was associated with prompt reestablishment of viral control. These study findings highlighted the role of SIV-specific CD8 T cells on both viral production in blood and SIV reservoir size measured in tissues (14). Such animal model experiments demonstrated the role of CD8 T cell function on the control of pre ART viremia and size of viral reservoir (total DNA load) following early ART.…”
Section: Influence Of Early Art Initiation On the Dynamics Of Hiv Spementioning
confidence: 55%
“…They further showed that repopulation of CD8 T cells was associated with prompt reestablishment of viral control. These study findings highlighted the role of SIV-specific CD8 T cells on both viral production in blood and SIV reservoir size measured in tissues (14). Such animal model experiments demonstrated the role of CD8 T cell function on the control of pre ART viremia and size of viral reservoir (total DNA load) following early ART.…”
Section: Influence Of Early Art Initiation On the Dynamics Of Hiv Spementioning
confidence: 55%
“…Other markers of T cell exhaustion include co‐inhibitory receptors Lymphocyte‐activation gene 3 (LAG‐3), CD160, and T‐cell immunoglobulin and mucin‐domain containing‐3 (Tim‐3) . It was recently shown that while virus‐specific CD8 + T cells are initially capable of cytolytic activity, the potential is significantly reduced after acute infection . Thus, while HIV‐specific CD8 + T cells appear to be necessary for the post‐peak decline in viremia during the acute infection, persistent exposure to antigen and chronic inflammation results in an exhausted phenotype, where cells are no longer capable of amounting an appropriate anti‐viral response against HIV therefore the infection remains.…”
Section: Cd8+ T Cells In Hiv and Siv Pathogenesismentioning
confidence: 99%
“…We next investigated whether the functional properties of HIV-specific CD8 + (24)(25)(26)(27)(28). While granzyme B production can be induced in memory CD8 + T-cells, this requires more than 24 hours of in vitro stimulation, whereas IFN-g is produced rapidly from both memory and effector CD8 + T-cells (24,34,35).…”
Section: Recent In Vivo Antigen Recognition By Nef-specific T-cellsmentioning
confidence: 99%
“…We first confirm that, in this cohort, T-cell responses to autologous reservoir viruses are well represented by a scalable IFN-g enzyme-linked immunospot (ELISPOT) assay, and show that these responses persist over years. Strikingly, the persistence of T-cell responses to the HIV-Nef protein (slopes of change) over 144 weeks were strongly and uniquely associated with the frequencies of infected cells that persisted on ART (22,23), and these responses disproportionately exhibited a cytotoxic effector functional profile, indicative of recent in vivo antigen recognition (24)(25)(26)(27)(28). These results conclusively reveal ongoing interactions between the immune system and the HIV reservoir over years of ART, with implications both for understanding HIV persistence, and designing interventions aimed at curing infection.…”
Section: Introductionmentioning
confidence: 99%